An HVDC inverter based on the Asymmetric Alternate Arm Converter with thyristor valves - Soto Sanchez, Diego; Pena, Ruben; Flores, Lorena; Andrade Aguero, Ivan Eric; Blasco-Gimenez, Ramon (My University, 2021)
The Modular Multilevel Converter (MMC) is one of the most practical topologies for integration of renewable energy power plants into the grid, through submarine HVDC cables and HVDC lines. Nonetheless, the MMC requires significant large DC storage capacitors. This work addresses the recently introduced Asymmetric Alternate Arm Converter (A3C), a hybrid MMC topology which uses modular arms only on the lower side of the main converter whereas the upper side uses only standard ON-OFF valves. The A3C offers a significant reduction in DC energy storage requirements and in the number of modules. In addition, it offers a less restricted operation than the Alternate Arm Converter (A2C), in terms of operating over a wide range of AC to DC voltage ratio, and the possibility of achieving both nearly sinusoidal AC current and nearly constant DC current. The principle of operation of the A3C, but in the inverter mode and using thyristor-based director switches, is revisited here and a suitable control strategy to demonstrate its operation is developed. Emphasis is place on switching off the thyristor valves in a soft commutation fashion. The method requires two A3C operating in interleaving fashion on the DC bus. Proposals are verified through simulation studies.
Keywords: hvdc; hybrid multilevel converter; modular multilevel converter; alternate arm converter